The Passionate Historian A Conversation with John Elliott. - Burton, Howard (Ideas Roadshow Conversations Ser., 2020)
This book is based on an in-depth filmed conversation between Howard Burton and John Elliott, Regius Professor of History Emeritus at the University of Oxford and Honorary Fellow of Oriel College, Oxford and Trinity College, Cambridge. This extensive conversation provides behind-the-scenes insights into how an undergraduate encounter with a 17th-century painting of The Count-Duke Olivares led John Elliott on a lifelong odyssey to study the history of Spain, Europe and the Americas in the early modern period to become one of the greatest Spanish historians of our age. This carefully-edited book.